2017
DOI: 10.13045/acupunct.2017089
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Intervention Studies on Acupuncture for Parkinson’s Disease

Abstract: [Abstract]Objectives : Thepurposeofthisstudywastoinvestigatetheeffectofacupuncturetreatment (AT)inthetendencyofincreaseoftheneedforATforthetreatmentofParkinson' sdisease (PD)worldwideandtoinvestigatetheadvancementsinATresearchinKoreaandthefuture directionsofresearchonthistopic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Acupuncture is 1 of the most popular CAM treatments for PD, and is reported to have the greatest benefit without adverse effects and without detrimentally affecting the PD Western medicine drug response. Acupuncture treatment of PD was reported to improve every aspect of functional daily life, including motor and neurological skills [2,11]. This current study employed acupuncture twice a day during the total treatment period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Acupuncture is 1 of the most popular CAM treatments for PD, and is reported to have the greatest benefit without adverse effects and without detrimentally affecting the PD Western medicine drug response. Acupuncture treatment of PD was reported to improve every aspect of functional daily life, including motor and neurological skills [2,11]. This current study employed acupuncture twice a day during the total treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…This current study employed acupuncture twice a day during the total treatment period. GV20, LR3, ST36, SP6 and GB34 acupoints were selected because they have been reported to be used in the treatment of PD [2]. Additionally, 4-6 ouch points, were selected to perform acupuncture on (as determined by tenderness or other pathological responses for some symptoms such as headache, dizziness, lower back pain, and leg numbness).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Korea, there has been an analysis of intervention studies for Parkinson's disease [3] and a review of acupuncture and moxibustion for the treatment of Parkinson's disease [4]. In China, research into oriental medicine treatments for Parkinson's disease has also been reported [5,6].…”
Section: Introductionmentioning
confidence: 99%